Konsep Keluarga Rukun Pada Tradisi Begalan Di Desa Kerandon Jawa Barat - Al Mustaqim, Dede; Munadilhaq, Ahmad; Fitriani, Novi; Putri Heryanto, Suci Nurlathifah (Ri'ayah: Jurnal Sosial dan Keagamaan, 2025)
This research aims to examine the concept of a harmonious family in the begalan tradition in Kerandon Village, West Java. The begalan tradition is a traditional tradition that has been passed down from generation to generation in Kerandon Village and has a deep meaning for the welfare of the family. The research method used is a qualitative approach using interviews, observation and document analysis as data collection techniques. The research results show that the begalan tradition has an important role in forming a harmonious family and strengthening social ties between family members. The symbolism in this tradition, such as the fight between Brandal Lokat Caya and Prince Bonang, the distribution of luggage, and the symbolic meaning of the objects used, reflect harmonious family values ​​such as cooperation, mutual respect and mutual cooperation. The novelty in this research lies in the in-depth analysis of harmonious family values ​​in the symbolic context of local culture which has not been revealed much in previous studies. These findings show that the begalan tradition is not only a cultural heritage, but also a medium for character formation and strengthening social values ​​in the family amidst changing times. The implications of the findings of this research indicate that the begalan tradition plays an important role in building a harmonious family and provides a forum for strengthening family ties and social values.